Habitat use by armadillos in agroecosystems of central Argentina: does plot identity matter? - Abba, Agustín Manuel (2016)
In agroecosystems, the use of cultivated plots by mammals depends on habitat structure as well as on the degree of species specialization. In the Pampas of Argentina, during the last 2-3 decades, there has been a continuing expansion of cropland. The aim of this study was to analyze how the identity and characteristics of agricultural plots may have affected the activity of 2 species of armadillos (Chaetophractus villosus and Dasypus hybridus) in a rural landscape. We carried out 4 sampling sessions between December 2011 and June 2013, surveying 175 plots during spring-summer and 194 during fall at 25 different sites in the Pampas of Buenos Aires province, Argentina. In each plot, we surveyed for signs (burrows and holes) along a 600×6 m transect in order to assess armadillo activity and measured 4 habitat structural variables. As expected, there were structural differences between types of agricultural plots. Across all plots, a total of 6,654 armadillo signs were found (C. villosus = 5,009, D. hybridus = 1,645). Generalized linear mixed models revealed that during both seasons, the type of plot explained much of the variation in armadillo activity, except during spring-summer for D. hybridus. C. villosus had higher use of plots with a longer history of non-tillage (e.g., soybean), while there was more evidence of D. hybridus activity in plots with less human intervention (e.g., grasslands), especially during fall. Overall, D. hybridus and C. villosus were more sensitive to the particular structural features of plots rather than to the kind of land use practiced (crop field or rangeland). These results have important implications for future management decisions in the Pampas region because during the last decades, farming of soybeans has expanded at the expense of grasslands, and this change appears to have differentially affected these 2 species of armadillos.